PENGARUH PENGGUNAAN MODEL AISAS DALAM MENINGKATKAN MINAT BELI PRODUK P - Diana Alya Jaelani; Roni Kastaman; Totok Pujianto (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
CV. ABC is a company in the food sector that promotes products on social media. However, along with the development of the internet, many other business actors have started to use social media to promote their products, which has led to competition between businesses. Therefore, CV. ABC must attract purchase intention by increasing the AISAS (Attention, Interest, Search, Action, Share) model in its social media marketing. Thus, this study aims to analyze how the influence of the AISAS model on social media relates to purchase intention. This research is categorized into quantitative analysis with a descriptive approach. The data used are primary and secondary. Primary data collection uses a questionnaire with a Likert scale of 1-5. The sampling technique was a purposive sampling of 140 respondents. The analysis technique used is the coefficient of determination test, F test, t-test, and multiple linear regression test processed with SPSS 25 software. The study's results prove the influence of the AISAS model (Attention, Interest, Search, Action, Share) on purchase intention is 0.679 or 67.9% and individually, namely Attention 0.160, Interest 0.200, Search 0.084, Action 0.251, and Share 0.102. The most dominant AISAS model variable influencing purchase intention is the Action variable which is indicated by the significance with the smallest value of 0.000 <0.05.